Floods Disaster Mitigation In Bojonegoro Regency - Nika Herawati; Setya Haksama; Mohammad Zainal Fatah (Universitas Airlangga, 2022)
Background: Many disasters occurred in Indonesia, especially in Bojonegoro Regency. Based on the results of the report from the Regional Disaster Management Agency (BPBD) of Bojonegoro Regency, the total incidence of flash floods since 2018-2020 has occurred 40 times. Bojonegoro Regency has an enormous flash flood potential if it was compared to other regencies in East Java. Based on this, the BPBD team prepared a contingency plan to implement flash floods disaster mitigation in Bojonegoro Regency.Objectives: Analyzing the handling of banjir bandang disaster risks carried out by the government of Bojonegoro Regency, among others, formulating policies and strategies in the context of handling flood victims.Methods: This research is a descriptive study using a qualitative approach in describing a contingency plan containing flash floods disaster mitigation at the Bojonegoro district government. This research was conducted using a purposive sampling technique. Thus, the researcher has determined the informants according to the criteria set, the Regional Disaster Management Agency (BPBD) team of Bojonegoro Regency.Results: Based on the results of the analysis contingency plan about flood disaster mitigation, it could be known that the risk management carried out by the Bojonegoro Regency government includes formulating policies and strategies in the context of handling flash floods victim.Conclusions: This study concludes a contingency plan which includes mitigation of flash floods risk management in Bojonegoro Regency is quite effective in handling risks to minimize the consequences.